Screening Models for Cardiac Risk Evaluation in Emergency Abdominal Surgery. I. Evaluation of the Intraoperative Period Risk based on Data from the Preoperative Period - Mikhail Matveev; Maria Milanova (Bioautomation, 2008)
A classification of intraoperative cardio-vascular complications (CVC) was performed, based on data from 466 patients subjected to emergency surgery, due to severe abdominal surgical diseases or traumas, in accordance with the severe criteria of ACC/AHA for CVC in noncardiac surgery. There were 370 intraoperative CVC registered, distributed as follows: groups with low risk (148), moderate risk (200), and high risk (22). Patient groups were formed, according to the CVC risk level, during the intraoperative period, for which the determinant factor for the group distribution of patients was the complication with the highest risk. Individual data was collected for each patient, based on 65 indices: age, physical status, diseases, surgical interventions, anaesthesiological information, intra and postoperative cardio-vascular complications, disease outcome, causes of death, cardiovascular disease anamnesis, anamnesis of all other nonsurgical diseases present, laboratory results, results from all imaging and instrumental examinations, etc. On the basis of these indices, a new distribution of the risk factors was implemented, into groups with different levels of risk of CVC during intraoperative period. This result is a solid argument, substantiating the proposal to introduce these adjustments for determining the severity of CVC in the specific conditions of emergency abdominal surgery.